Log2(x-2)+log2(x-3)=1
log2(x-2)×(x-3)=1
x-2>0
x>2
x-3>0
x>3
(x-2)×(x-3)=2¹
x²-3x-2x+6=2
x²-5x+6-2=0
x²-5x+4=0
D=(-(-5))²-4×1×4=25-16=9
x1=(-(-5)-√9)/2×1=(5-3)/2=2/2=1
x2=(-(-5)+√9)/2×1=(5+3)/2=8/2=4
так по условию х>3
следовательно решением нашего уравнени
является только:
х2=4.
log2(x-2)×(x-3)=1
log2(4-2)×(4-3)=1
log2(2×1)=1
log2(2)=1
13759-9859=3900
3900:100=39
307*480=147360
39*17=663
147360+663=148023
Log3(x/3x-2)= log3(3)
x/3x-2 = 3
x - 9x + 6 = 0 -8x + 6 = 0 x = 3/4
3x - 2 > 0 x > 2/3
Ответ: 3/4
Угол М=50, угол Р=40, угол К=90. Сумма=50+40+90=180